The Influence of Human Development Index, Economic Growth, and Minimum Wage on Poverty with Zakat as A Moderation Variable in ASEAN-4 Countries (International Forum of Researchers and Lecturers, 2025)
This study examines the influence of the Human Development Index (HDI), economic growth, and minimum wage on poverty levels in ASEAN-4 countries (Indonesia, Malaysia, Thailand, and the Philippines) from 2016 to 2024, with zakat as a moderating factor. The main objective is to analyze how zakat mitigates the effects of HDI, economic growth, and minimum wage on poverty. Using a quantitative approach, the research applies path analysis and moderation regression to evaluate these relationships. The findings reveal that zakat effectively moderates the relationship between economic growth and poverty, as well as between HDI and poverty, indicating that zakat plays a substantial role in reducing poverty through improvements in human development and economic advancement. However, the results also show that zakat does not moderate the effect of the minimum wage on poverty levels. This suggests that while zakat is an essential tool for alleviating poverty, it cannot replace the need for sound labor market policies, job creation, and fair wage distribution. These insights highlight the potential of integrating zakat into broader poverty reduction strategies, especially those targeting human development and economic growth. Policymakers in ASEAN countries could leverage zakat as part of comprehensive socio-economic programs to enhance the effectiveness of poverty alleviation efforts. The absence of moderation in the minimum wage context underscores the importance of considering multiple dimensions of poverty, where wage policies, employment opportunities, and social welfare programs must complement zakat to produce sustainable results. Overall, this study contributes to the discourse on the intersection between Islamic economic instruments and development policies, offering empirical evidence of zakat’s role as a moderating variable in poverty reduction strategies.